2010
DOI: 10.1017/s0022215110002392
|View full text |Cite
|
Sign up to set email alerts
|

How reliable is visual assessment of the electrically elicited stapedius reflex threshold during cochlear implant surgery, compared with tympanometry?

Abstract: There was almost no difference between reflex thresholds measured with the two different techniques under the same intra-operative conditions. Therefore, we conclude that differences between intra- and post-operative thresholds are not due to the use of different measuring techniques. The main reason for such differences is probably the influence of intra-operative narcotics on reflex thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
(12 reference statements)
0
13
0
1
Order By: Relevance
“…Therefore, fitting methods based on objectively measured parameters have been sought. Different researchers tried to use electrically-evoked auditory brainstem responses, electrically-evoked stapedius reflex thresholds or measurements of the electrically-evoked compound action potentials (ECAP) [Mittal and Panwar, 2009;Muhaimeed et al, 2010;Pau et al, 2011;Van Den Abbeele et al, 2012]. Even though the correlations of these measures with the behavioural thresholds (T levels) and hearing comfort levels (C levels) are relatively weak [Holstad et al, 2009;Potts et al, 2007;Smoorenburg et al, 2002;Tao et al, 2011] for particular electrodes, fittings based on the objective profiles with subsequent behavioural adaptation of the 'shift and tilt' [Hughes et al, 2001;King et al, 2006;Smoorenburg et al, 2002] are widely used and currently rank among the best available options.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fitting methods based on objectively measured parameters have been sought. Different researchers tried to use electrically-evoked auditory brainstem responses, electrically-evoked stapedius reflex thresholds or measurements of the electrically-evoked compound action potentials (ECAP) [Mittal and Panwar, 2009;Muhaimeed et al, 2010;Pau et al, 2011;Van Den Abbeele et al, 2012]. Even though the correlations of these measures with the behavioural thresholds (T levels) and hearing comfort levels (C levels) are relatively weak [Holstad et al, 2009;Potts et al, 2007;Smoorenburg et al, 2002;Tao et al, 2011] for particular electrodes, fittings based on the objective profiles with subsequent behavioural adaptation of the 'shift and tilt' [Hughes et al, 2001;King et al, 2006;Smoorenburg et al, 2002] are widely used and currently rank among the best available options.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility for the child population would be visual intraoperative assessment of the stapedius reflex, a simple, fast, and objective procedure. Even though intraoperative ESRT was higher than postoperative values, possibly due to the action of anesthetic agents that can weaken the stapedius reflex muscle during surgery (Ruth et al, 1982;Gnadeberg et al, 1994;Pau et al, 2011), this procedure provides important information both at the time of surgery and postoperative activation of the CI (Baysal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Electrically evoked stapedius reflex thresholds (ESRT) are promising, given that the research has shown a relationship between these thresholds and the maximum comfort level in adults and children with CI (Stephan and Welzl-Müller, 2000). The ESRT can be obtained easily in the clinic, using standard immittance measurement instrumentation, or intraoperatively, via direct observation or immittance measurements (Pau et al, 2011). It can be recorded for a majority of patients (Hodges et al, 1999;Gordon et al, 2004;Van Den Abbeele et al, 2012) and generally lies around the comfort level, thus below the uncomfortable level (Jerger et al, 1988;Hodges et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…[11] ESR is a quick and non-invasive method to verify the integrity of auditory nerve functions. [12] ESR thresholds could be used to extract useful information, as several studies have indicated an association between these thresholds and the assessment of maximum comfort level (C-level) in adults and children with CIs. [13][14][15][16] The correlation between the values obtained objectively and values assessed by the behavioral method has been extensively investigated.…”
Section: Original Articlementioning
confidence: 99%